The Professionalism of the Indonesian National Police in Addressing Gang related Disturbances in Traditional Markets Within the Jurisdiction of Bogor Regency - Wiguna, Wendy Setia; Nuraeny, Henny; Gilalo , Jacobus Jopie (Jurnal Hukum Indonesia, 2026)
This study examines the professionalism of the Indonesian National Police in handling thuggery disturbances in traditional markets within the jurisdiction of Bogor Regency, along with the forms of legal protection provided to business actors and the broader impacts of thuggery on market security, order, and economic activity. The research employed a normative juridical method with a statute approach, relying on primary, secondary, and tertiary legal materials collected through library research. The findings reveal that police professionalism in addressing thuggery has not been fully optimal. Although the police have carried out both preventive and repressive measures in accordance with applicable regulations, the handling remains reactive, incidental, and unsustainable, failing to eliminate thuggery practices comprehensively. Legal protection provided by local governments and law enforcement officials tends to be normative and administrative in nature, lacking effective integration and neglecting victim assistance and recovery aspects. Thuggery has been proven to produce significant negative impacts on traditional market environments, including the erosion of security and public order, the emergence of informal power structures that supplant formal authority, increased operational burdens on small traders through illegal levies, and declining market competitiveness. Furthermore, thuggery undermines public trust in law enforcement institutions and discourages investment in the micro, small, and medium enterprise sector. This research concludes that an integrated, cross-sectoral approach is essential, encompassing strengthened whistleblower protection, intensified security measures, improved inter-agency coordination, and policy-level reforms in traditional market governance to effectively eradicate thuggery and ensure sustainable legal protection for market business actors.